Analysis of Securities Crowdfunding from the Perspective of Maqashid Al-Shari'ah - Ulumuddin, Moh. (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2024)
Background. Shari’ah fintech has great potential to promote financial inclusion and improve access to financial services that comply with Islamic principles. The challenges in financial literacy, regulation, and Shari’ah compliance still need to be addressed to maximize this potential. Aim. This study aims to describe and analyze the implementation of fintech in Shari’ah-compliant securities crowdfunding in Indonesia and evaluate its alignment with the principles of Maqashid al-Shari’ah. Method. The research employs a descriptive-analytical approach with a qualitative method. Primary data sources include literature, regulations issued by the Otoritas Jasa Keuangan (OJK), and industry reports related to Shari’ah fintech. Data collection is conducted through document studies, analyzing relevant regulatory and industry documents. The data is analyzed using thematic analysis to identify patterns and key themes. Result. The implementation of Shari’ah fintech in Indonesia generally aligns with the core objectives of Maqashid al-Shari’ah, namely the protection of religion, life, intellect, lineage, and wealth. Shari’ah fintech platforms successfully avoid elements of riba (interest), gharar (uncertainty), and maysir (speculation), adopting financing models like mudharabah and musyarakah. However, several challenges remain, including inconsistent regulations, cybersecurity issues, inadequate technological infrastructure, and low public financial literacy regarding Shari’ah fintech. To enhance transparency and security, technologies like blockchain and smart contracts are recommended.